Monogeneans of fish of the Mingechevir Reservoir of the Kura River basin - Mahmudova, P. (The Journal of V.N.Karazin Kharkiv National University. Series «Biology», 2019)
In 2010–2013, a study on fish of the Mingechevir Reservoir of the Kura River basin, for infestation with parasites belonging to the Monogenea class was conducted. 297 specimens of fish were subjected to parasitological dissections. These fish belong to the following 23 species: roach – Rutilus rutilus caspius, Caucasian chub – Leuciscus cephalus orientalis, asp – Aspius aspius taeniatus, tench – Tinca tinca, Kura nase – Chondrostoma cyri, Kura khramulya – Capoeta capoeta, chanari-barbel – Luciobarbus capito, goldfish – Carassius auratus gibelio, carp – Cyprinus carpio, Kura beardie – Barbatula brandti, Transcaucasica spined loach – Cobitis taenia satunini, catfish – Silurus glanis, mosquito fish – Gambusia affinis, pike – Sander lucioperca, big headed goby – Neogobius kessleri gorlap, monkey goby – N. fluviatilis pallasi. As a result of the research, 34 species of monogeneans belonging to 3 orders of 4 families and 5 genera were identified. The overwhelming majority (32 species) of monogeneans found are parasitic on the gill petals of fish, from two to six species are also found on the surface of the body and fins, in the nasal cavity of fish. Of the found monogeneans, 24 species (70.6%) are specific for one species or one genus of fish. It has been established that monogeneans parasitizing on several hosts infect the main of them more than others fish, and the intensity of invasion of fish with large sizes was higher than that of relatively small fish. By their origin, 23 species or 67.7% of all species belong to the boreal lowland faunistic complex. According to the ecological groups of this complex, they are distributed as follows: in the Ponto-Caspian group – 17 species, in the Palaearctic and amphiboreal groups – 3 species each. The Middle East faunistic complex is represented by six, the Indian lowland complex is represented by three, and the Ponto-Caspian marine complex by two species. Among the monogeneans of fish of the Mingechevir Reservoir, two species, Dactylogyrus extensus and D. vastator destroy gill petals of their hosts and cause their diseases. They are the cause of the mass death of juvenile fish.